2019
DOI: 10.26502/jnr.2688-8521004
|View full text |Cite
|
Sign up to set email alerts
|

Essential Metal-Based Nanoparticles (Copper/Iron NPs) as Potent Nematicidal Agents against Meloidogyne spp.

Abstract: Root-knot nematodes (Meloidogyne spp.) cause great economic impact in the sector of agriculture while the number of existing commercial nematicides has been drastically reduced. The metal-based nanoparticles offer new possibilities as agrochemicals. In the current study, we shed light on the role of copper/iron based nanoparticles as bioactive agents against the root knot nematode Meloidogyne spp; along with the plant enhancement properties on the nematode infested host. Same sized PEGylated Cu, CuFe and CuFeO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Nanoparticles are also extremely useful in agriculture where they can alleviate the effects of plant diseases and are active components in nano-fertilisers [11][12][13][14][15][16][17][18]. Liu and Lal [15] classify nano-fertilisers according to the following categories: (i) macro-nutrient nano-fertilisers; (ii) micro-nutrient nano-fertilisers that include nanoparticles which are mainly oxides such as ZnO, CuO, Fe 2 O 3 , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles are also extremely useful in agriculture where they can alleviate the effects of plant diseases and are active components in nano-fertilisers [11][12][13][14][15][16][17][18]. Liu and Lal [15] classify nano-fertilisers according to the following categories: (i) macro-nutrient nano-fertilisers; (ii) micro-nutrient nano-fertilisers that include nanoparticles which are mainly oxides such as ZnO, CuO, Fe 2 O 3 , etc.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at 1600 and 1400 cm −1 in the spectra of alginate and X-(Cu–Fe)/Alg correspond to the vibrations of asymmetric and symmetric C– O –C, as reported [ 36 , 37 ]. Additionally, in the spectrum of bare Cu–Fe, the peaks at 1448 and 1126 cm −1 indicate metal-hydroxide (Metal-OH; Fe–OH/Cu–OH) vibrations [ 38 , 39 ], while the peaks at 883 and 788 cm −1 are attributed to iron oxide (Metal-O; Fe–O), and those at 622 and 558 cm −1 denote copper oxide (Metal-O; Cu–O) [ 40 , 41 ]. Upon investigating potential interactions in the FTIR spectra of Cu–Fe loaded into alginate by mass ratio, it was observed that high Cu–Fe loading exhibited more stretching vibration bands at 1600 and 1400 cm −1 , indicating increased polymer cross-linkage [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%